Analytical solutions for Navier-Stokes Equations with Caputo Fractional Derivative - Mariam, NOUIOUA; Supervisor: Hamza, MIHOUBI (Mohamed Boudiaf University of M'sila, 2025)
In this work, we will use the residual power series (RPS) method to generate the solution of the nonlinear time fractional Navier-Stokes equation with Caputo fractional derivative in two dimensions in the form of a rapidly convergent series,where we adopted the definition of generalized Fractional calculus operators, including those of Riemann-Liouville.Hadamard,Katugampula of the Caputo type. We gave an illustrative application to demonstrate the effectiveness and leverage of the proposed method, where numerical results and graphical representations reveal that the proposed method performs extremely well in terms of efficiency and simplicity and it can be utilized to solve more problems in the field of non-linear fractional differential equations (FDEs).
Keywords: Fractional Navier–Stokes equations; Caputo fractional derivative; Fractional power series; Mittag-Leffler function